2012
DOI: 10.1155/2012/186891
|View full text |Cite
|
Sign up to set email alerts
|

Seed Cryopreservation of Some Medicinal Legumes

Abstract: Seed survival after storage in liquid nitrogen (–196°C) was examined in 12 wild medicinal legume species occurred Far East of Russia. Dry seeds of all species survived cryostorage without loss of viability. Initial germinability varied from 3 to 85%. The stimulatory effect of cryogenic temperature on germination, with or without subsequent chemical scarification, was observed in all species studied with deep physical dormancy or heterogeneous levels of hardseededness. Frozen seeds demonstrated higher germinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
(31 reference statements)
1
5
0
4
Order By: Relevance
“…Even more, as was observed in three species, cryostorage enhanced germination. Similar response was reported for several orchid seeds (Nikishina et al, 2007;Popov et al, 2004); for Pyrus communis (Reed et al, 2001), Halimium atriplicifolium, Helianthemum apenninum, Helianthemum squamatum (P erez-García and Gonz alez-Benito, 2008), Angelica ursina, Oxytropis chankaenis, Oxytropis retusa (Kholina and Voronkova, 2008), Elaeis guineensis (Camillo et al, 2009), Passiflora suberosa, and Passiflora edulis (Ara ujo et al, 2016); and for wild medicinal legume species (Kholina and Voronkova, 2012) after seed cryostorage. It has been suggested that LN exposure may enhance the germination of treated seeds by breaking seed dormancy or softening of the seed coat (Kholina and Voronkova, 2008;Reed et al, 2001).…”
Section: Discussionsupporting
confidence: 69%
“…Even more, as was observed in three species, cryostorage enhanced germination. Similar response was reported for several orchid seeds (Nikishina et al, 2007;Popov et al, 2004); for Pyrus communis (Reed et al, 2001), Halimium atriplicifolium, Helianthemum apenninum, Helianthemum squamatum (P erez-García and Gonz alez-Benito, 2008), Angelica ursina, Oxytropis chankaenis, Oxytropis retusa (Kholina and Voronkova, 2008), Elaeis guineensis (Camillo et al, 2009), Passiflora suberosa, and Passiflora edulis (Ara ujo et al, 2016); and for wild medicinal legume species (Kholina and Voronkova, 2012) after seed cryostorage. It has been suggested that LN exposure may enhance the germination of treated seeds by breaking seed dormancy or softening of the seed coat (Kholina and Voronkova, 2008;Reed et al, 2001).…”
Section: Discussionsupporting
confidence: 69%
“…The use of slow thawing of cryostored seeds without losses has been observed frequently, as presented by Farias et al (2006) in jatoba (Hymenaea courbaril L.), Rocha et al (2009) in four cotton cultivars (Gossypium hirsutum L.), and by Kholina & Voronkova (2012) in 12 native species from eastern Russia.…”
Section: Sucrose Use In Thawing Deep Frozen Seedsmentioning
confidence: 99%
“…Растения O. lanata сформировали семена с довольно высокой степенью твердосемянности (табл. 3, контроль), близкой к таковой O. chankaensis, у которого всхожесть семян в контроле не превышала 6,0 % (Kholina, Voronkova, 2012;Voronkova, Kholina, 2010). Нарушение непроницаемости кожуры при обработке серной кислотой привело к активному прорастанию семян (табл.…”
Section: прорастание семян O Lanata и ихunclassified
“…Воздействие ультранизкой температуры с последующим размораживанием было аналогично воздействию серной кислоты и, по-видимому, также связано с повреждением семянной кожуры. Преодоление экзогенного типа покоя под действием сверхнизких температур отмечено ранее для видов Oxytropis (Kholina, Voronkova, 2012;Voronkova et al, 2008;Voronkova, Kholina, 2010) и других дикорастущих бобовых (Kholina, Voronkova, 2012;Pence, 1991;Perez-Garsia, 2008;Salomăo, 2002).…”
Section: показательunclassified